Pengaruh Pemberian Pupuk Organik Cair Urine Sapi Terhadap Pertumbuhan dan Hasil 3 (tiga) Varietas Terong (Solanum melongena L.): Kata kunci: Terong, POC, Varietas - Riana Kusuma; Sartono Joko Santosa; Kharis Triyono (Innofarm:Jurnal Inovasi Pertanian, 2022)
The purpose of this study was to see if there was an effect of giving cow urine liquid organic fertilizer on the growth and yield of three varieties of eggplant (Solanum melongena L.). The activity will be held on December 14, 2021 until February 5, 2022 at the Research Garden and Land Collection, Faculty of Agriculture, Slamet Riyadi University, which is located on Jl. Jaya Wijaya No. 384, Kadipiro Village, Banjarsari District, Surakarta. Split plot design (RPT) or split plot design used in this study consisted of 2 factors and then replicated 3 times. The first factor is the variety (V) consisting of 3 levels including the Jelita variety (V1), Silila variety (V2) and the Teho variety (V3), the second factor is POC volume treatment with 4 levels, namely no volume (D0), volume 150 ml (D1), volume 300 ml (D2), volume 450 ml (D3). The data obtained were studied using Analysis of Variation (Anova) and then the Tukey test was carried out at the 5% level. After the research, liquid organic fertilizer of cow urine did not show a significant effect on the growth and yield of three eggplant varieties.